Customer experience for dummies: It is illegal under Indian law to export this book from India - Barnes, Roy; Kelleher, Bob (New Delhi Wiley India Pvt. Ltd., 2019)
A positive customer experience is absolutely essential to keeping your business relevant. Today's business owners need to know how to connect and engage with their customers through a variety of different channels, including online reviews and word of mouth. Customer Experience For Dummies helps you listen to your customers and offers friendly, practical, and easy-to-implement solutions for incorporating customer engagement into your business plans and keep the crowds singing your praises.